3-D numerical investigation on buoyancy-induced flow and heat transfer from a hollow horizontal steel cylinder with finite wall thickness. (16th September 2020) - Dash, Manoj Kumar; Dash, Sukanta Kumar
Abstract: In the present work, numerical study on the buoyancy induced flow and heat transfer around a hollow horizontal cylinder with finite wall thickness either suspended in air or placed on ground has been performed. The effects of the Rayleigh Number (10 3 ≤ Ra ≤ 10 7 ), length to outer diameter ratio (0.1≤ L/D ≤ 20) and the thickness ratio (0.4≤ d/D ≤ 0.9) of the cylinder have been studied. The effect of the pertinent parameters on average Nusselt number ( Nu ), local Nusselt number, and the ratio of heat loss from individual surface to total heat loss has been elucidated graphically. The flow and the heat transfer characteristics around the cylinder have been delineated with the help of velocity vectors and the thermal contours. The average Nu for cylinder suspended in air is always found to be more than an identical cylinder placed on the ground up to Ra of 10 6 . However, for Ra = 10 7 and d/D ≥ 0.8, the average Nu for cylinder placed on the ground is marginally more than the cylinder suspended in the air up to L/D = 0.8. Hence forward, the trend reverses. On comparing, the average Nu for the outer surface of the cylinder suspended in air and placed on the ground, the average Nu is found to be marginally higher for the former case. However, for the inner surface, the average Nu is found to be higher for the latter case. The thickness ratio has a profound influence on the average Nu typically at a low L/D and high L/D ratios ( L/D ≤ 0.5 and L/D ≥ 5). The present study also proposes correlations for the average Nu as a function of Ra, L/D, and d/D both for cylinder in air and ground separately.